Axiological bases for a quality academic policy: UNED case - Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2019)
The construction of the theory of values or axiological bases that support statements for the management of educational practices performed UNED - Costa Rica of an academic policy that strengthens the institutional mission and aspirations of providing excellent academic quality.  Use grounded theory Glaser and Strauss (1967) to produce substantive theory emerging from the qualitative and open, axial and reflective coding for conceptualizing the premises axiology are disclosed and discussed in a panel informant.  The main contribution is to discuss that educational practices are the phenomenological element by which one can differentiate the distance education model, its generations, ideological values, academic management, public value and the establishment of key meta-theoretical elements to ensure the management of quality from institutional policies.  Carr (2002) affirms that in the educational practices not only the thematic content is established, for Freire (1999) the ideological and public values ​​that characterize the teaching - learning process are reinforced.  Hermeneutically, quality is based on public value based on the missionary objectives of the institution, ontologically the search for excellence is the core category that facilitates the construction process.Keywords: University at a distance; Quality of education; Qualitative analysis; Epistemology
Keywords: University at a distance; Quality of education; Qualitative analysis; Epistemology